The Criminal Responsibility of the Juvenile Murderer - Martin A. Frey (Washington University Law Quarterly, 1970)
Juvenile courts—special courts having jurisdiction over juvenile offenders—were created which professed as their objective an intense desire to consider the child's welfare and provide for his redemption rather than punishment for his misconduct? Behind this apparent unity of purpose, contrary positions exist. The juvenile court jurisdiction may or may not affect incapacity. If it does, the effect is to change the common law age for complete incapacity and those ages between which there is a rebuttable presumption of incapacity. If juvenile court jurisdiction does not affect incapacity, then it may only postpone criminal prosecution and punishment until the offender passes beyond the juvenile court's jurisdiction.
Keywords: Criminal responsibility; Juvenile courts; Criminal intent; Murder